Performance Measurement Supply Chain Management (SCM) Using the Supply Chain Operation Reference (SCOR) Method at PT X - Alfi Hidayati; Farida Pulansari (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
In the world of the fertilizer industry in Indonesia, there are some of problems in the process of planning, procurement and, delivery of materials that adversely affect the company's operations. One approach to fixing this problem is to use a SCOR strategy that is effective in improving the supply chain. PT. X is one of the fertilizer companies whose current condition is that there are problems in planning to meet the needs for production supporting materials so which has the potential to hinder fertilizer production. This is because PT X has not carried out an analysis that hinders demand planning or the supply chain as a whole. Thus, researchers can measure the value of effectiveness in the supply chain to improve targets that have not been achieved. In this research, a scoring method called SCOR was used which included AHP weighting. Fifteen key performance indicators (KPI) were generated based on the five SCOR model indicators used in processing, namely data plan, source, make, delivery, and return. With a final score of the SCM performance level of 86.872, which is included in the Good category. However, this value can still be improved so that it is included in the excellent category, namely >90. So inecessary to identify KPI indicators that have performance values that are not yet optimal, and to make suggestions for improvements to increase PT X SCM performance values.